Ablative therapies for small renal tumors - Adamowicz, Jan; Tworkiewicz, Jakub; Siekiera, Jerzy; Drewa, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2013)
Ablative therapies of renal tumors are steadily gaining popularity in clinical practice due to the many benefits they offer to patients. Moreover, ablative procedures hold promise in the field of uro-oncology for the best compromise between low invasiveness, high efficacy and advantages in terms of procedural costs. Reported outcomes with ablative therapies for small renal tumors are excellent and without significant differences for surgical procedures based on nephron-sparing surgery. Nevertheless, these methods for treatment of small renal tumors should still be confined to carefully selected patients. This review discusses the currently used ablative techniques in urology.